MAKNA DEMOKRASI PANCASILA - Hutabarat, Dany Try Hutama; Sari, Sekar Nawang; Kamil, Tiara; Ramadhan, Wulan Suci; Ambarwati, Eny Ayu; Alfathni, Tri Nia; Fadhila, Nur; Septiningrum, Shafira; Aflita, Riri; Ltubing, Junita Mutiara Sari; Hidayat, Agung; Setiawan, Diski; Pangestu, Inderawan (Transpublika Publisher, 2021)
Democracy is a political system that has been adopted by practically every country in the world over the course of history. Freedom and equal rights are not just important political ideals in liberal countries, but they are also important in communist countries, which are known as people's democracies.. While our country adheres to the political system of Pancasila democracy, Indonesia follows the political system of Pancasila democracy, i.e., the original democracy of the Indonesian nation with the values contained in it derived from the Indonesian people's philosophy of life, and whose implementation is written in the preamble and body of the 1945 Constitution.